Introduction to Two Dimensional Mappings - Leonel, Edson Denis [UNESP] (My University, 2021)
This chapter is dedicated to the introduction of two dimensional mappings. We start with a discussion of two dimensional linear mappings obtaining their fixed points and discussing their stability. Then we introduce two dimensional nonlinear mappings and discuss how to obtain the fixed points and characterize their stability by using the linearised equations. We also present an algorithm to obtain the Lyapunov exponents. At the end we discuss two examples of well known mappings.